2022 revised European recommendations for the coding of the basis of diagnosis of cancer cases in population-based cancer registries - Visser, Otto; Kościańska, Beata; Caetano dos Santos, Florentino Luciano; Cuccaro, Francesco; Forjaz, Gonçalo; Michalek, Irmina Maria; Mousavi, Mohsen; Sulkowska, Urszula; Martos, Carmen; Giusti, Francesco (Frontiers in Oncology, 2023)
The basis of diagnosis recommendations for population-based cancer registries aim to provide a standardized coding tool that reflects the certainty of cancer diagnosis, especially when pathological confirmation is lacking. The proportion of clinical diagnoses serves as an indicator of data quality. Given the evolving nature of diagnostic techniques, regular revision of the basis of diagnosis rules is crucial. To address this, a working group comprising representatives from the steering committee and member registries of the European Network of Cancer Registries was established. The original 1999 recommendations were comprehensively reviewed, resulting in the publication of an updated version. These new recommendations came into effect for incident cancer cases starting from January 1, 2023. The updated recommendations comprise an adapted code list for the basis of diagnosis, optional codes for histology cases, revisions related to flow cytometry, liquid biopsy, and cytogenetic/molecular testing, consolidation of histology codes 6 and 7, introduction of a new code 8 for cytogenetic/molecular confirmation, and establishment of new criteria for registering specific morphology codes in cancers lacking pathological confirmation.